A Drama Theory Analysis of Host-Guest Interaction In Peer-To-Peer Accommodation - Lisa Putri Kusuma; Pri Hermawan (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
Peer-to-peer economy is characterised by asymmetric information, economy risks, and social uncertainty that may be arisen in unpredictable time. In hospitality industries, peer-to-peer accommodation allows people to rent unoccupied room or properties to stranger (i.e with the introduction of AirBnB etc). In studying the customer perception, drama theory provides a powerful framework for understanding role of emotion in an interaction. A dilemma analysis is an essential feature of drama theory approach and is described here. This paper provides further application of drama theory II, and reviews host-guest interaction by analysing dilemmas in pre-booking stage with the case if AirBnB. The conclusion is that drama theory is applicable to recognise dilemmas in host-guest interaction in peer-to-peer accommodation.